How and when do frequent daily work interruptions contribute to or undermine daily job satisfaction? A stress appraisal perspective - Körner, Barbara; Debus, Maike Elisabeth; Wu, Chia‐Huei; Kleinmann, Martin (Wiley, 2025)
This research brings a broad stress appraisal lens to the study of frequent daily work interruptions, offering a unifying theoretical framework to answer why and when work interruptions can engender negative or positive reactions, thereby explaining seemingly contradictory empirical findings. Drawing on cognitive appraisal theory, we propose that frequent interruptions simultaneously trigger hindrance and threat appraisals, which are associated with negative affective reactions (daily negative affect), and challenge appraisal promoting progress toward daily goals (daily work goal progress). These reactions subsequently shape attitudes (daily job satisfaction) later in the day. Furthermore, when an individual appraises frequent interruptions as controllable (i.e., secondary appraisal), they are less likely to view them as a hindrance or threat and more likely to view them as a challenge. Daily diary data from two studies show that frequent work interruptions can elicit hindrance, threat, and challenge appraisals, and threat appraisal is found to increase daily negative affect and undermine daily work goal progress and, thus, daily job satisfaction. In Study 1, interruptions facilitate daily work goal progress. We also discuss the results of secondary appraisal as a moderator. Taken together, our research provides a broad lens of stress appraisal to expand future research on interruptions.
Keywords: control appraisal; frequent daily work interruptions; stress appraisal